LIVING AL-QUR’AN DI MEDIA SOSIAL: STUDI ETNOGRAFI VIRTUAL PADA AKUN TIKTOK @MY INSPIRATION - Abdan Syakuro; Ahmad Gungun Fariq; Ainun Nafisa; Choirul Azam Firdaus; Ecep Ismail; Asep Abdul Muhyi (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This research explores the reception of the Qur'an in the digital era through a TikTok platform called My Inspiration using a descriptive qualitative method. The analysis focuses on several videos or content related to three recommended practices for having children, the meaning of Surah At-Talaq verses 2–3 commonly referred to as the "Ayat of a Thousand Dinars"as well as the interpretation and recitation of Surah Ad-Dhuha, and understanding the tests given by Allah. This study highlights contemporary methods of da'wah through social media and also emphasizes life dynamics, including how to attain a good life and remain patient when tested by Allah in various ways. The findings reveal that the video content offers an aesthetic and exegetical approach, presenting religious concepts with visually engaging elements, simple and easily understood language, and depictions grounded in everyday life. This research complements the limitations of previous studies and demonstrates the adaptation of Qur'anic messages within the context of modern life and public response in the digital era.